A Blind and Militant Attachment: Russian Patriotism in Comparative Perspective - Mikhail Alexeev; William Pyle (Center for Economic Studies and ifo Institute (CESifo), 2022)
Much of the literature on patriotic sentiment in post-Soviet Russia leans on the results of public opinion surveys administered to Russian citizens. Absent a comparison group, such evidence, while helpful, can leave one adrift in trying to assess the significance of any particular polling result. Here, we draw on a shared set of questions from multiple waves of the Inter-national Social Survey Program's National Identity and Role of Government modules, as well as the World Values Survey, to benchmark the responses of Russians to those of citizens in a diverse group of middle and high income countries. This exercise highlights that while Russians are not unusual in the degree to which they have a benign attachment to and/or pride in their country, they stand out for espousing a patriotism that has remained consistently blind and militant since at least the mid-1990s. We speculate as to the underlying cause and highlight a potential consequence: the nature of Russian patriotism has lowered the cost to the Russian leadership of military aggression.
Keywords: P00; P20; 330; patriotism; Russia; post-imperial syndrome